Caffeine ingestion in competitive road cyclists in Australia - Orr, R.; Stannard, S. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
It is well established that caffeine improves prolonged endurance exercise in the laboratory setting1. Little data is available on the incidence of caffeine ingestion amongst athletes during competition2, including dosage, optimal timing of intake and preferred method of administration. Anecdotal evidence suggests that caffeine ingestion is prevalent amongst competitive road cyclists in Australia. The aims of this study are to determine i) the preferred method of caffeine intake before and during competition ii) the amount of caffeine taken by riders in order to provide a perceived ergogenic effect, and iii) the timing of intake that the athletes perceive as being optimal.